2002
DOI: 10.1542/peds.109.5.846
|View full text |Cite
|
Sign up to set email alerts
|

Jaundice as an Early Diagnostic Sign of Urinary Tract Infection in Infancy

Abstract: A UTI was found in 7.5% of asymptomatic, afebrile, jaundiced infants younger than 8 weeks old. In addition, infants with the onset of jaundice after 8 days of age or patients with an elevated conjugated bilirubin fraction were more likely to have a UTI. Therefore, we recommend that testing for a UTI be included as part of the evaluation in asymptomatic, jaundiced infants presenting to the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
97
6
22

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 32 publications
15
97
6
22
Order By: Relevance
“…In another study by Biyikli et al [9] in Turkey, the high rate (63%) of E-coli was reported among 71 jaundiced infants who were diagnosed and treated for UTI. Garcia and Nager [2] and Omar et al [10] reported other organisms, with lower frequencies, which are Enterobacter, Streptococcus viridans, Enterococcus, Streptococcus group B and Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study by Biyikli et al [9] in Turkey, the high rate (63%) of E-coli was reported among 71 jaundiced infants who were diagnosed and treated for UTI. Garcia and Nager [2] and Omar et al [10] reported other organisms, with lower frequencies, which are Enterobacter, Streptococcus viridans, Enterococcus, Streptococcus group B and Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…In one large cohort study based on data from neonatal intensive care units, there was a 13 % rate of a positive blood culture collected within three days of the urine culture with the same pathogenic organism [5]. Bacteremia and sepsis have been well-documented as a cause of neonatal jaundice in seriously ill newborns and jaundice may be one of the first signs of bacterial sepsis in neonates in the first few days of life [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürde term bebekler için semptom-İYE ilişkisine bakıldı-ğında ateş (%20-40), büyüme geriliği (%15-43), sarılık (%3-41), kusma (%9-41), ishal (%3-5) ve kötü beslenme (%3-5) azalan sıklıkta görülmektedir (8)(9)(10)(11). Bazı bebeklerde İYE'nin ilk işareti sarılık olabilir (12). Arıkan ve ark.nın (13) 2009 yılında yaptık-ları bir çalışmada, yenidoğanda İYE semptomları sıklık sırasına göre sarılık, kusma, ateş ve emmeme olarak saptanmıştır.…”
Section: Discussionunclassified
“…; [13] semptomsuz indirekt hiperbilirübine-mili 102 hastanın %8'inde üriner sistem enfeksiyonu tespit etmişlerdir. Garcia ve Nager'in [14] çalışmasında iki aydan küçük 160 semptomsuz indirekt hiperbilirü-binemili hastanın %7.5'inde pozitif idrar kültürü tespit etmişlerdir. Shahian ve ark.…”
Section: Bulgularunclassified